Elevated Methylation of FOXP3 (Forkhead Box P3)-TSDR (Regulatory T-Cell–Specific Demethylated Region) Is Associated With Increased Risk for Adverse Outcomes in Patients With Acute Coronary Syndrome. Issue 3 (September 2019) - Zhu, Ling; Jia, Lei; Liu, Zhongwei; Zhang, Yong; Wang, Junkui; Yuan, Zuyi; Hui, Rutai
Abstract : Demethylation of the forkhead box P3 ( FOXP3 ) corresponds with stability of FOXP3 expression and immunosuppressive function of regulatory T cells (Tregs). Previous studies have demonstrated that reduction in Tregs is associated with acute coronary syndrome (ACS). The aim of this study was to establish the relationship between methylation level of FOXP3-TSDR (Treg-specific demethylated region) and clinical outcomes of ACS. We first evaluated the prognostic significance of methylation levels of FOXP3-TSDR in patients with ACS (n=171). Then, we explored the possible mechanism of methylation levels of FOXP3-TSDR on clinical outcomes of ACS in vivo. We analyzed methylation of FOXP3-TSDR, percentage of Tregs in total peripheral blood, and atherosclerotic lesions in aortic root in ApoE −/− mice (n=48; 6 groups). During the follow-up of 4.5±0.8 years, survival free of major adverse cardiovascular events was the lowest in the highest tertile of FOXP3-TSDR methylation (log-rank P =0.004). Multivariate analysis showed that FOXP3-TSDR methylation was independently and positively related to major adverse cardiovascular events (adjusted hazard ratio, 2.13; 95% CI, 1.21–3.75; P =0.009). We observed a duration-dependent increase in the methylation levels of FOXP3-TSDR in mice fed with Western diet at a period of 0, 3, 6, 9, 12, and 15 weeks. Elevated methylation levels of FOXP3-TSDR were significantly correlated of severity of atherosclerosis. We further found that FOXP3-TSDR methylation was inversely related to the percentages of Treg TGF-β (transforming growth factor-β) and IL (interleukin)-10 levels. Our results indicate that elevated methylation levels of FOXP3-TSDR are associated with increased risk for adverse outcomes in patients with ACS. Abstract : Supplemental Digital Content is available in the text.